1998
DOI: 10.1212/wnl.51.2.627
|View full text |Cite
|
Sign up to set email alerts
|

Topiramate increases cerebral GABA in healthy humans

Abstract: Topiramate (TOP) is a novel anticonvulsant drug with multiple mechanisms of action used in the treatment of epilepsy. Measurements of cerebral GABA were obtained in six controls using 1H MRS at baseline and at 3 and 6 hours following the administration of 3 mg/kg of TOP. Brain GABA concentrations rose by 72% at 3 hours and by 64% at 6 hours compared with baseline (p < 0.004). This study demonstrates that TOP significantly increases human cerebral GABA concentrations in healthy individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
70
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(72 citation statements)
references
References 3 publications
1
70
1
Order By: Relevance
“…In humans, TPM increases cerebral GABA, homocarnosine, and pyrrolidinone concentrations (18,19). These potential antiepileptic mechanisms were not expected from in vitro and rodent model studies (13).…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…In humans, TPM increases cerebral GABA, homocarnosine, and pyrrolidinone concentrations (18,19). These potential antiepileptic mechanisms were not expected from in vitro and rodent model studies (13).…”
mentioning
confidence: 89%
“…Patients with epilepsy treated daily with TPM have higher brain GABA levels than do patients treated with carbamazepine (CBZ), gabapentin (GBP), lamotrigine (LTG), phenobarbital (PB), phenytoin (PHT), primidone (PRM), or valproate (VPA) (19). In healthy human subjects, TPM raises brain GABA within 3 h of the first, oral, 200-mg dose (18). The acute pharmacodynamic effects of TPM on GABA metabolism have not been reported in patients with epilepsy.…”
mentioning
confidence: 99%
“…Several groups have actively pursued the measurement of GABA, both at rest and under the modulation of a variety of agents. 70,[73][74][75][76][77][78][79][80][81][82] Note that all of these studies have been performed either at fields higher than 1.5 T or with special spectral editing sequences, or a combination of both.…”
Section: Amino Acidsmentioning
confidence: 99%
“…212 We are not aware of any neuroimaging study that examined GABA receptors after treatment with mood stabilizers in mood disorder patients. In vivo MRS studies found an increase in human GABA levels after gabapentin, 213 topiramate, 214 and vigabatrin administration, 215 which are new anticonvulsants suggested to be effective in particular cases of mood disorders.…”
Section: Gabaergic Modulation In the Treatment Of Mood Disordersmentioning
confidence: 99%
“…Hyperforin, a major component of hypericum extract, which has been reported to be effective as antidepressant, 245 may inhibit GABA synaptosomal uptake in rat forebrain, elevating GABA levels. 246 It is stimulating to note that Griffin 98,102 No association between GABA A subunit genes and lithium-responsive bipolar patients 185,218 Valproate m in rat brain 199À203 and cultured neurons 203 m GABA turnover 190,191 and GAD activity 204 174,175 NEW AC m in rat brain 192,193 m GABA A receptor b3 m in human brain 213,214 subunit in rat hippocampus 172 165,253 IMAO m in rat brain 224,237,239,240 kGAD and GABA-T in rat brain 224 2 in rat brain 224,225 2 in rat frontal cortex 230 Other and Mellon 247 have reported that certain SSRIs directly alter the activity of neurosteroidogenic enzymes in the CNS. As the authors suggested, this effect may lead to increased production of neurosteroids in the brain, potentially modulating GABA-associated behaviors.…”
Section: 218mentioning
confidence: 99%